Mortality Patterns in Patients with Multiple Trauma: A Systematic Review of Autopsy Studies. - Roman Pfeifer; Michel Teuben; Hagen Andruszkow; Bilal M Barkatali; Hans-Christoph Pape (PLoS ONE)
Purpose A high percentage (50%-60%) of trauma patients die due to their injuries prior to arrival at the hospital. Studies on preclinical mortality including post-mortem examinations are rare. In this review, we summarized the literature focusing on clinical and preclinical mortality and studies included post-mortem examinations. Methods A literature search was conducted using PubMed/Medline database for relevant medical literature in English or German language published within the last four decades (1980-2015). The following MeSH search terms were used in different combinations: "multiple trauma", "epidemiology", "mortality ", "cause of death", and "autopsy". References from available studies were searched as well. Results Marked differences in demographic parameters and injury severity between studies were identified. Moreover, the incidence of penetrating injuries has shown a wide range (between 4% and 38%). Both unimodal and bimodal concepts of trauma mortality have been favored. Studies have shown a wide variation in time intervals used to analyze the distribution of death. Thus, it is difficult to say which distribution is correct. Conclusions We have identified variable results indicating bimodal or unimodal death distribution. Further more stundardized studies in this field are needed. We would like to encourage investigators to choose the inclusion criteria more critically and to consider factors affecting the pattern of mortality.